Facile Synthesis of Nickel Oxide Nanoparticles and Their Structural, Optical and Magnetic Properties - An, G.; Babu1, ha; Ravi1, G.; Arivan, M.; Navaneethan2, M.; Hayakawa2, Y. (Asian Journal of Chemistry, 2013)
Nickel oxide nanoparticles have been successfully synthesized through microwave assisted reaction of nickel nitrate, sodium hydroxide and citric acid as a capping agent. The structure, morphology, optical and magnetic properties of the NiO products are characterized by XRD, TEM, FTIR, UV-VIS and VSM. XRD results revealed that the resultant sample showed cubic structure with average grain size less than 25 nm. Analysis of FTIR spectra confirmed the composition of the product and the existence of nickel oxide vibration. TEM image demonstrated that the obtained nickel oxide nanoparticles with size less than 25 nm. The optical absorption band gap of nanocrystalline NiO was estimated to be 3.21 eV. Magnetic measurement showed that the nickel oxide nanoparticles exhibit ferromagnetic behaviour at room temperature (300 K). Based on experimental observation and analysis, a possible mechanism is proposed to enrich the properties of NiO nanostructured material for various applications such as storage devices, gas sensors, etc.